Identification of Excretory â Secretory Sporozoite Antigens of Eimeria tenella with Monoclonal Antibody - Prastowo, J; Nurcahyo, W; Kurniasih, Kurniasih; Wasito, R (ANIMAL PRODUCTION, 2005)
The research done specifically to identified the. Eimeria tenella excretory-secretory sporozoit antigen by using the monoclonal antibody reaction instead. Eimeria tenella excretory-secretory sporozoit antigen. The 107 sporozoits were obtained from existation of 5x107 oocysts with 25 ml tripsin and sodium taurocholat. Excretion - secretion antigen were preparated by freezing and thawing and then be isolated with ice bath 20 second, 20 meter of amplitude as the further treatment.Â  Determinating the excretion -secretion sporozoit protein by using BCA-test. While the visualization sporozoit protein antigen by SDS-PAGE. Monoclonal antibody were produced through hybridization between B BALB/c limphosit immunized with Eimeria tenella excretion-secretion sporozoite antigen and myeloma cells. The monoclonal antibody identificationÂ  of excretion â secretion antigen were done through western blott. The visualization of protein molecule weight of Eimeria tenella sporozoit were resulted 20 protein fraction, included 14, 16, 17, 18, 20, 24, 26, 32, 34, 36, 39, 43, 47, 56, 65, 67, 76, 87, 94, and 96 KDa. There were 12 kinds of monoclonal antibody could be produced from these proteins. While the 5 hybridoma immunoblotting resulted specific reaction by the appearances of reaction ribbon obviously, there were MABset 1 which identified protein epitop with 14.7 KDa of molecule weight,Â  MAbset 2 which identified protein epitop with 43 KDa of molecule weight, MAbset 3 which identified protein epitop with 42 KDa of molecule weight, MAbset 4 which identified protein epitop with 47 KDa of molecule weight and MAbset 5 which identified protein epitop with 90 KDa of molecule weight. As the conclusion, five of excretion-secretion sporozoit antigen were proper immunogen to stimulate the hospest immunity. (Animal Production 7(2): 95-100 (2005)Â Key Words: Sporozoit, Antigent, Eimeria tenella, Coccidiosis